EP537 Dyskerin plays a negative role in endometrial epithelial cell proliferation and is associated with poor survival in endometrial cancer. (1st November 2019) - Alnafakh, R; Saretzki, G; Adishesh, M; DeCruze, SB; Midgley, A; Drury, J; Hapangama, D
Abstract : Introduction/Background: The dramatic increase of endometrial cancer (EC) incidence with the associated rise in mortality demands the discovery of reliable prognostic and therapeutic biomarkers. High telomerase is an essential feature of most EC, and is needed for telomere maintenance. TERT and TERC components of telomerase holoenzyme is extensively studied yet Dyskerin, the third component of telomerase, in the endometrium is not previously evaluated. The aim of the study is to evaluate the function of dyskerin in EC cells and to examine its prognostic value in EC. Methodology: The transient over-expression of DKC1 gene in Ishikawa EC cells line on proliferation was studied in vitro using direct flow cytometry. Immunoblotting and immunoflourescence confirmed the overexpression of dyskerin protein. A human endometrial samples from 173 women were examined with immunohistochemistry to assess prognostic relevance of dyskerin expression in EC. Results: DKC1 overexpression down-regulated cell proliferation in ISK cells. Immunoblotting confirmed that dyskerin protein was elevated in transfected cells 24hr after the transfection compared with the negative controls. Exogenous dyskerin localised in cytoplasm and nucleus of transfected cell while endogenous dyskerin was located only in nucleus and has a specific morphological feature. Human endometrium expresses dyskerin ( DKC1 ) and dyskerin protein levels are significantly reduced in ECs (p=0.0002) when compared with healthy postmenopausal endometrium and negatively correlated with ki67 proliferative index. Low dyskerin immunoscores were associated with worse outcomes, suggesting a prognostic relevance. In silico analysis of the TCGA uterine cancer dataset further confirms changes in DKC1 gene expression in EC with a prognostic significance. Conclusion: Our data suggest dyskerin to have a negative role on endometrial epithelial cell proliferation and confirms an aberrant expression and a possible prognostic relevance in EC. Interventions aimed at modulating dyskerin may therefore provide novel therapeutic options in EC. Disclosure: Nothing to disclose.